2022
DOI: 10.3390/jcm11041131
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopy-Assisted Reduction and Internal Fixation versus Open Reduction and Internal Fixation for Glenoid Fracture with Scapular Involvement: A Retrospective Cohort Study

Abstract: Background: We investigated the superiority of arthroscopy-assisted reduction and internal fixation (ARIF) to open reduction and internal fixation (ORIF) for treating glenoid fracture with scapular involvement. Methods: We retrospectively enrolled patients with glenoid fracture who underwent ARIF or ORIF from 2010–2020. Radiographic outcomes were assessed, and clinical outcomes (active range of motion [ROM], visual analog scale [VAS], Constant, and Disabilities of the Arm, Shoulder and Hand [DASH]) were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Interestingly, Scheibel et al also found a high rate of relevant intra-articular concomitant lesions in about 78% of cases. Lin et al found better pain outcomes of arthroscopic treatment compared to open surgery as it enabled accurate management of associated intra-articular lesions that were found in 50% of cases of the arthroscopic group [14]. In the current study, in 13 of 23 patients (57%) relevant concomitant lesions were found intra-articularly requiring arthroscopic treatment.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Interestingly, Scheibel et al also found a high rate of relevant intra-articular concomitant lesions in about 78% of cases. Lin et al found better pain outcomes of arthroscopic treatment compared to open surgery as it enabled accurate management of associated intra-articular lesions that were found in 50% of cases of the arthroscopic group [14]. In the current study, in 13 of 23 patients (57%) relevant concomitant lesions were found intra-articularly requiring arthroscopic treatment.…”
Section: Discussionsupporting
confidence: 47%
“…Surgical treatment of glenoid fractures remains challenging. Recent evidence has shown that open surgery is associated with higher complication rates and worse clinical outcomes than arthroscopic procedures, probably due to the soft tissue trauma requiring detachment of the subscapularis tendon [4,14].…”
Section: Discussionmentioning
confidence: 99%
“…In China, Professor Tian pioneered anatomical studies and concluded that axillary approach surgery is less invasive, with concealed and beautiful incisions, and can achieve good clinical outcomes. [7] Among the 13 scapular glenoid fractures in this study, Ideberg type Ia scapular glenoid fractures accounted for a relatively large number of 10 cases. Unlike bony Bankart injuries, most of the Ideberg type Ia scapular glenoid fractures involved in this paper are anterior and inferior to the scapular glenoid.…”
Section: Anatomical Characteristics and Technical Points Of The Axill...mentioning
confidence: 72%
“…[6] Professor Tian found that axillary approach surgery for the anterolateral rim of scapular glenoid fractures (mainly Ideberg type Ia) has the advantages of minimal trauma, broad exposure, reliable internal fixation, and concealed appearance. [7] From December 2020 to January 2022, we used the axillary approach to treat 13 patients with scapular glenoid fractures with satisfactory results. This study discussed the curative effect and matters needing attention of this operation through retrospective analysis of the data of this group of patients, as reported as follows.…”
Section: This Study Was Supported By the "Cultivation Plan Of High-le...mentioning
confidence: 99%
See 1 more Smart Citation